Utilization of financial ratios in selected financial models to predict financial distress among food manufacturing companies in the Philippines - Chen, Simon Hongying G. (Animo Repository, 2023)
This study aimed to assess the accuracy of utilizing financial ratios in models such as the comparative ratio analysis, emerging market score model, and logistic regression models for predicting financial distress among private food manufacturing companies in the Philippines during the year 2014-2019. The findings of the study indicated that all three research methodologies achieved acceptable prediction accuracy rates above the 50% cut-off threshold. This suggests that financial ratios can effectively gauge early signs of financial distress. Additionally, the study provides insights for practitioners in using the same analytical process to assess financial risk. While limitations exist, this research bridges theoretical concepts with practical applications, contributing to the understanding of financial distress prediction in the food manufacturing industry.